2009
DOI: 10.1590/s1517-83822009000100013
|View full text |Cite
|
Sign up to set email alerts
|

Spread of Metallo-β-lactamases: screening reveals the presence of a BLA SPM-1 gene in hospital sewage in southern Brazil

Abstract: Of 396 Pseudomonas aeruginosa strains isolated from hospital sewage, the blaSPM-1 gene was confirmed in nine. This is the first report of environmental P. aeruginosa strains carrying the blaSPM-1 gene in Brazil. The carbapenem resistance, already disseminated among clinical isolates, has been detected among environmental isolates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Resistance to the ␤-lactam antibiotics is frequently observed in the clinical setting and is commonly due to the expression of enzymes that can hydrolyze these compounds, namely, ␤-lactamases (13,(49)(50)(51)(52). P. aeruginosa clinical isolates often harbor acquired ␤-lactamases, particularly those of the oxacillinase type (class D) and the metallo-␤-lactamase IMP and VIM types (class B) (23,25,(53)(54)(55)(56)(57)(58). Chromosomally, P. aeruginosa carries a cephalosporinase, AmpC, that provides intrinsic resistance and that can be expressed at high levels in the presence of ␤-lactams (24, 59, 60) and a carbapenemase, PIB-1, that is reported to be ubiquitous but expressed at low levels in strain PAO1 (26).…”
Section: Resultsmentioning
confidence: 99%
“…Resistance to the ␤-lactam antibiotics is frequently observed in the clinical setting and is commonly due to the expression of enzymes that can hydrolyze these compounds, namely, ␤-lactamases (13,(49)(50)(51)(52). P. aeruginosa clinical isolates often harbor acquired ␤-lactamases, particularly those of the oxacillinase type (class D) and the metallo-␤-lactamase IMP and VIM types (class B) (23,25,(53)(54)(55)(56)(57)(58). Chromosomally, P. aeruginosa carries a cephalosporinase, AmpC, that provides intrinsic resistance and that can be expressed at high levels in the presence of ␤-lactams (24, 59, 60) and a carbapenemase, PIB-1, that is reported to be ubiquitous but expressed at low levels in strain PAO1 (26).…”
Section: Resultsmentioning
confidence: 99%
“…Although the antimicrobial susceptibility profiles found in our work showed reduced susceptibility to beta-lactams among the strains, few studies have related non-clinical isolates of Pseudomonas genus to this group of resistance genes. Fuentefria et al (2009) have identified nine strains of P. aeruginosa positive to gene bla SPM-1 , isolated from samples of untreated hospital effluents in Brazil. Quinteira et al (2005) found, in a sample of urban sewage receiving untreated hospital effluents, an environmental strain of P. pseudoalcaligenes VIM-2 producer.…”
Section: Discussionmentioning
confidence: 99%
“…restricted to the hospital setting, a fact that emphasizes the importance of surveying environmental strains that might act as a source and/or reservoir of resistance genes with clinical relevance (1,5,7,13) and have the potential for dissemination in communities through river environments (1,10).…”
mentioning
confidence: 99%